Advances in Legionella Control by a New Formulation of Hydrogen Peroxide and Silver Salts in a Hospital Hot Water Network - Luna Girolamini (Pathogens, 2019)
Legionella surveillance is an important issue in public health, linked to the severity of disease and the difficulty associated with eradicating this bacterium from the water environment. Different treatments are suggested to reduce Legionella risk, however long-term studies of their efficiency are lacking. This study focused on the activity of a new formulation of hydrogen peroxide and silver salts, WTP828, in the hospital hot water network (HWN) to contain Legionella contamination during two years of treatment. The effectiveness of WTP828 was tested measuring physical-chemical and microbiological parameters such as Legionella, Pseudomonas aeruginosa (P. aeruginosa), and a heterotopic plate count (HPC) at 36 °C. Legionella isolates were identified by serotyping and genotyping. WTP 828 induced a reduction in Legionella−positive sites (60% to 36%) and contamination levels (2.12 to 1.7 log10 CFU/L), with isolates belonging to L. pneumophila SG1 (ST1 and ST104), L. anisa and L. rubrilucens widely distributed in HWN. No relevant contamination was found for other parameters tested. The long-term effect of WTP828 on Legionella containment suggest the easy and safe application of this disinfectant, that combined with knowledge of building characteristics, an adequate environmental monitoring and risk assessment plan, become the key elements in preventing Legionella contamination and exposure.